MANAGEMENT OF REFORESTATION AND RESTORATION OF BIODIVERSITY - Ms. Samita Barik, Ms. Namrata Singh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
There is a need to address certain gaps in the field of research related to reforestation: researchers have studied the reaction of diversity, structure & species studies of species to the recovery of the forest area in Africa, indicating that species but not genetic variation has improved with restoration period. The Bayesian Network was used which emphasizes the advantages of this approach in helping managerial decisions. Cost-effectiveness research, for example, may add to the process of maximizing revegetation projects, helping natural resource managers by enabling them to see how to preserve the best resources with their small maintenance budgets in a straightforward manner. Given the high degree of uncertainty in the models built here, more refining may be accomplished by ongoing data gathering & convergence with the Bayesian Networks. It was found that, in cleared areas, restore intervention will contribute to an improvement of up to 20 percent in beetle species wealth and up to 13 percent in reptile species wealth compared to comparatively modest increases (6 percent) in other ecosystems for around the same investment cost..